“ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN (Studi Kasus Pada Bank-bank Umum Go Public yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016)” - Rieta Octavia Pancarani, 14.05.52.0224; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2018)
This research aims to exam the factors that influence the profitability of banking company listed in the IDX on period 2012-2016. This research based on the annual report of go-public banking company listed on IDX. The sampling method using purposive sampling, that sample determination technique by using certain criteria. The relationship or influence between variables is explained by using multiple linier regression analysis method and hypothesis test (t-test). The result of the research shows that variable of Capital Adequacy Ratio (CAR) has no influence to Return on Asset (ROA), Operating Expense to Operating Income (BOPO) and Loan To Deposit Ratio (LDR) has negative and significant influence to Return on Asset (ROA), Net Interest Margin (NIM) has positive and significant influence to Return on Asset (ROA), Non Performing LoanandGood Corporate Governance has positive and insignificant influence to Return on Asset (ROA). Keyword: CAR, BOPO, NIM, LDR, NPL, GCG, and ROA.